PENGEMBANGAN MEDIA QUIET BOOK BERBASIS MULTIMODAL UNTUK NUMERASI SISWA KELAS I SEKOLAH DASAR - Dewi Apriliani Yusuf; Siti Raihan; Samsuriyani Eka Putri Atjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low numeracy skills of first-grade elementary school students, particularly in basic addition and subtraction operations, due to the lack of interactive and concrete learning media. This study aims to develop a Multi-modal-based Quiet Book as a learning medium for number concepts that is valid, practical, and effective. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were first-grade students at SD Inpres Panaikang II/1. Data collection techniques included observation, interviews, and questionnaires. The results showed that the Multi-modal Quiet Book was declared "Very Valid" by material experts with a percentage of 91% and media experts with 98%. Practicality tests by teachers reached 100%, and student responses in small and large group trials reached 96% and 97%, respectively. Based on these results, it can be concluded that the Multi-modal-based Quiet Book is highly suitable for use as a learning medium to improve the numeracy skills of first-grade elementary school students.